Green synthesis and characterization of iron oxide nanoparticles for the removal of heavy metals (Cd2+ and Ni2+) from aqueous solutions with Antimicrobial Investigation - Abdelrahman Mohamed; R. R. Atta; Amna A. Kotp; Fatma I. Abo El-Ela; Hany Abd El-Raheem; Ahmed Farghali; Dalal Hussien M. Alkhalifah; Wael N. Hozzein; Rehab Mahmoud (Scientific Reports, 2023)
Abstract Clove and green Coffee (g-Coffee) extracts were used to synthesize green iron oxide nanoparticles, which were then used to sorb Cd2+ and Ni2+ ions out of an aqueous solution. Investigations with x-ray diffraction, Fourier-transform infrared spectroscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, nitrogen adsorption and desorption (BET), Zeta potential, and scanning electron microscopy were performed to know and understand more about the chemical structure and surface morphology of the produced iron oxide nanoparticles. The characterization revealed that the main component of iron nanoparticles was magnetite when the Clove extract was used as a reducing agent for Fe3+, but both magnetite and hematite were included when the g-Coffee extract was used. Sorption capacity for metal ions was studied as a function of sorbent dosage, metal ion concentration, and sorption period. The maximum Cd2+ adsorption capacity was 78 and 74 mg/g, while that of Ni2+ was 64.8 and 80 mg/g for iron nanoparticles prepared using Clove and g-Coffee, respectively. Different isotherm and kinetic adsorption models were used to fit experimental adsorption data. Adsorption of Cd2+ and Ni2+ on the iron oxide surface was found to be heterogeneous, and the mechanism of chemisorption is involved in the stage of determining the rate. The correlation coefficient R2 and error functions like RMSE, MES and MAE were used to evaluate the best fit models to the experimental adsorption data. The adsorption mechanism was explored using FTIR analysis. Antimicrobial study showed broad spectrum antibacterial activity of the tested nanomaterials against both Gram positive (S. aureus) (25923) and Gram negative (E. coli) (25913) bacteria with increased activity against Gram positive bacteria than Gram negative one and more activity for Green iron oxide nanoparticles prepared from Clove than g-Coffee one.